A Policy-into-Practice Intervention to Increase the Uptake of Evidence-Based Management of Low Back Pain in Primary Care: A Prospective Cohort Study - Slater, Helen (Public Library of Science, 2012)
BACKGROUND: Persistent non-specific low back pain (nsLBP) is poorly understood by the general community, by educators, researchers and health professionals, making effective care problematic. This study evaluated the effectiveness of a policy-into-practice intervention developed for primary care physicians (PCPs). METHODS: To encourage PCPs to adopt practical evidence-based approaches and facilitate time-efficient, integrated management of patients with nsLBP, we developed an interdisciplinary evidence-based, practical pain education program (gPEP) based on a contemporary biopsychosocial framework. One hundred and twenty six PCPs from primary care settings in Western Australia were recruited. PCPs participated in a 6.5-hour gPEP. Self-report measures recorded at baseline and at 2 months post-intervention included PCPs' attitudes, beliefs (modified Health Care Providers Pain and Impairment Relationship Scale (HC-PAIRS), evidence-based clinical practices (knowledge and skills regarding nsLBP management: 5-point Likert scale with 1 =  nil and 5 =  excellent) and practice behaviours (recommendations based on a patient vignette; 5-point Likert scale). RESULTS: Ninety one PCPs participated (attendance rate of 72%; post-intervention response rate 88%). PCP-responders adopted more positive, guideline-consistent beliefs, evidenced by clinically significant HC-PAIRS score differences (mean change  = −5.6±8.2, p<0.0001; 95% confidence interval: −7.6 to −3.6) and significant positive shifts on all measures of clinical knowledge and skills (p<0.0001 for all questions). Self management strategies were recommended more frequently post-intervention. The majority of responders who were guideline-inconsistent for work and bed rest recommendations (82% and 62% respectively) at pre-intervention, gave guideline-consistent responses at post-intervention. CONCLUSION: An interprofessional pain education program set within a framework that aligns health policy and practice, encourages PCPs to adopt more self-reported evidence-based attitudes, beliefs and clinical behaviours in their management of patients with nsLBP. However, further research is required to determine cost effectiveness of this approach when compared with other modes of educational delivery and to examine PCP behaviours in actual clinical practice.